Особливості фіксації логічного пізнання фразеологічними варіантами - Артеменко, Г. (Лексикографічний бюлетень, 2011)
The article discusses the features of idiom’s variants, components of which vary only in derivational means, connotative nuances of semantics or general denotative meanings. These units become interchangeable synonyms in a particular idiomatic context; depending on the degree of stability components are logically / illogically interchangeable in an idiom. Selecting specific phraseological units among a number of variants is caused by objective conditions of communication, linguistic competence of the speaker, his territorial or social group.